Epidemiological comparison of three pneumonia epidemics in a single hospital over 10 years - Eun-Kyung Kim; You-Sook Youn; Jung-Woo Rhim; Myung-Seok Shin; Jin-Han Kang; Kyung-Yil Lee (Korean Pediatric Society, 2015)
PurposeMycoplasma pneumoniae (MP) pneumonia epidemics have occurred in 3- to 4-year cycles in Korea. We evaluated the epidemiologic characteristics of MP pneumonia in Daejeon, Korea, from 2003 to 2012.MethodsWe retrospectively analyzed 779 medical records of children (0-15 years of old) with MP pneumonia admitted to our institution and compared the data from 3 recent epidemics.ResultsIn 779 patients, the mean age and male-to-female ratio were 5.0±2.2 years and 1:1, and most cases were observed in autumn. There were three epidemics during the study period, in 2003, 2006-2007, and 2011. In our comparison of the three epidemics, we found no differences in mean age, the male-to-female ratio, hospital stay, or the rate of seroconverters during hospitalization. All three epidemics began in early summer and peaked in September 2003 and 2011 and in October 2006 and then gradually decreased until the next year's spring season, although the 2006 epidemic extended further into 2007. The peak age groups in the children in 2003 and 2006 were 3-6 year-olds (57.5% and 56%, respectively), but in the 2011 epidemic, the peak group was 1-4 year-olds (46.5%). The proportion of the <2 years of age group was 20%, 15.7% and 28.8%, and >10 years of age group was 5.2%, 13.8%, and 14.8% of total patients, respectively.ConclusionMP pneumonia outbreaks occurred every 3-4 years. The pattern of 3 recent epidemics was similar in demographic characteristics and seasonality with some variations in each outbreak.